PENGEMBANGAN TEKNOLOGI INTERNET DALAM ADMINISTRASI PERSURATAN: MEMBANGUN SISTEM SURAT OTOMATIS - Yani, Ahmad; Alimsyah, Andi Saiful (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2025)
Mail administration is one of the important aspects of academic governance, but the manual process is often time-consuming, prone to errors, and difficult to track. This research aims to develop an automated letter system based on internet technology using the Google platform (Google Forms, Google Sheets, and Google Docs, as well as the Autocrat extension) in the Physical Education, Health, and Recreation Department. The research method uses a research and development (R&D) approach with the stages of needs analysis, design, implementation, and system evaluation. The research results show that this Google-based system can automatically generate letters in Doc or PDF format in less than 1 minute, with almost zero typing errors, and the archives are neatly stored in the cloud. This system is considered effective for improving the efficiency and accuracy of correspondence administration in the PJKR Department.